Sulfur–oleyl amine platelet derivatives with liquid crystalline behavior. Issue 72 (12th December 2018) - Tzitzios, Vasileios; Dimos, Konstantinos; Lelidis, Ioannis; Boukos, Nikos K.; Wadi, Vijay S.; Basina, Georgia; Nounesis, George; Alhassan, Saeed M.
Abstract : A novel sulfur-based platelet derivative was synthesized by reacting elemental sulfur with oleyl amine. Abstract : A novel sulfur-based platelet derivative was synthesized by reacting elemental sulfur with oleyl amine. The sulfur–oleyl amine (S–OA) derivative has an ionic salt form, layered morphology and forms a highly lamellar structure. Polarized optical microscopy (POM) clearly shows the birefringent lyotropic liquid crystalline behavior of the S–OA platelets dispersions.